Design, Analysis and Fabrication of Space Frame Chassis for Amphibious Hybrid Vehicle - Hassan, Muhammad Zahir; Alehan, Muhammad Nadzeer; Md Isa, Muhammad Fahmi; Abdul Manaf, Muhammad Zaidan (2013)
This paper explain the designed and development of space frame chassis for amphibious hybrid vehicle (AHV). Catia V5 R20 software is used for the designing and analysing before constructing the space frame chassis structure. Once the results of the analysis satisfied, the fabrication process is implemented. Hand lay-up method applied in the fabrication process of the chassis with the combination of bark wood, fibre glass E-class and epoxy resin. The general process involves in the fabrication process are cutting, drilling and fittings The chassis then assemble with brake system, drive shaft system, steering linkage system, suspension system and engine system. Good designs for manufacturing (DFM) practices have been implemented to assemble the chassis with all other AHV components.